IMPACT OF SOCIAL MEDIA ON THE MENTAL HEALTH OF YOUNG ADULT MALES IN GUWAHATI, ASSAM (CAHIERS MAGELLANES-NS, 2024)
This cross-sectional investigation examined the association between social media consumption and mental health outcomes among young adult males residing in Guwahati, Assam. Participants were categorized into three distinct age cohorts (18-32 years) and evaluated for levels of depression, anxiety, and stress using the DASS-42 assessment tool. Additionally, data was collected on participants' social media usage patterns through a pre-structured questionnaire. The results revealed that the 28-32 year age group exhibited the highest prevalence of severe depression and severe stress. Importantly, the use of Instagram was significantly correlated with both severe and moderate levels of anxiety and depression across all age groups. These findings underscore the potential detrimental impact of social media, particularly the use of Instagram, on the mental well-being of young adult males.